Answer:
it's your first answer of
y= (-7/8)x + 1/2
30(-2/5)²(5/8) = 30*(4/25)*(5/8) = 30*4/(5*8) = 3
Answer:
the correct solution is -8x + 9.
Step-by-step explanation:
The system of the linear systems of equation using substitution is;
- x = 2, y = 2
- x = -20, y = -1
<h3>Linear equation</h3>
3x-y=4
x+2y=6
from (2)
x = 6 - 2y
substitute into (1)
3x-y=4
3(6 - 2y) - y = 4
18 - 6y - y = 4
- 6y - y = 4 - 18
-7y = -14
y = 2
Substitute into
x+2y=6
x + 2(2) = 6
x + 4 = 6
x = 6 - 4
x = 2
2. 2x-y= -39
x+y= -21
From (2)
x = -21 - y
substitute into
2x-y= -39
2(-21 - y) - y = -39
-42 - 2y - y = -39
- 2y - y = -39 + 42
- 3y = 3
y = 3/-3
y = -1
substitute into
x+y= -21
x + (-1) = -21
x - 1 = -21
x = -21 + 1
x = -20
3. 2x+y =11
6x-5y =9
Learn more about linear equation:
brainly.com/question/4074386
#SPJ1
Answer:
3p³ + 2p² – 3p – 11
Step-by-step explanation:
From the question given above, the following data were obtained:
Side 1 (S₁) = –1(p + 5)
Side 2 (S₂) = 2(p² – 3)
Side 3 (S₃) = 3p³ – 2p
Perimeter (P) =?
The perimeter of the triangle can be obtained as follow
P = S₁ + S₂ + S₃
P = –1(p + 5) + 2(p² – 3) + 3p³ – 2p
Clear bracket
P = –p – 5 + 2p² – 6 + 3p³ – 2p
Rearrange
P = 3p³ + 2p² – 2p – p – 6 – 5
P = 3p³ + 2p² – 3p – 11
Therefore, the perimeter of the triangle is 3p³ + 2p² – 3p – 11